Impact of Market and Entrepreneurial Orientation on Batik MSMEs’ Performance in Yogyakarta - Artha, Bhenu; Putri, Anggun (Profesional Muda Cendekia Publishing, 2024)
Research Aims: In an organization, there are several factors that can affect business performance, including orientation, entrepreneurial orientation, utilization of social media and marketing capability. Based on the urgency above, this study focuses on exploring indicators that can effectively affect business performance and continuity in the current technological era in batik MSMEs. The purpose of this study is to provide an overview of the influence of antecedents on MSME performance so as to provide an overview of indicators that can effectively improve the performance of batik MSMEs in Yogyakarta. Design/methodology/approach: This research design uses a quantitative research method with an associative problem formulation. The type of research used is explanatory research. The number of respondent samples was 250 leaders or people in charge of various batik craft UMKM in Region of Yogyakarta Province. Data collection through the distribution of questionnaires with a face-to-face method between respondents and researchers. The analysis of this study uses the Structural Equation Modeling (SEM) method using AMOS. Research Findings: The results of this study are that market orientation, entrepreneurial Orientation, and use of social media have an effect on the marketing capability and business performance of Batik MSMEs in Yogyakarta. Theoretical Contribution/Originality: This study provides an overview of the importance of market orientation and entrepreneurial Orientation for improving a company's business performance. The novelty of this study's results is that it shows that the use of social media and marketing capability are also indicators that play a role in improving business performance.